Prevalensi Kelainan Refraksi pada Anak Remaja Kelas X di SMA Rex Mundi Manado - Putri, Angeline J.; Umboh, Anne M. S.; Najoan, Imelda H. M. (Universitas Sam Ratulangi, 2024)
Abstract: Uncorrected refractive errors are a leading cause of vision impairment across all age groups. In Indonesia, adolescents aged 15-18 years face the risk of eye health issues due to excessive use of electronic devices, particularly during the COVID-19 pandemic. This study aimed to obtain the prevalence of refractive errors among adolescents. This was a quantitative and descriptive study using a cross-sectional design. Subjects were tenth-grade students at SMA Rex Mundi Manado. selected through total sampling. The results showed that there were 225 subjects who underwent refractive error screening and met the inclusion criteria. Out of 225 subjects, 176 had emmetropia (normal vision) and 49 had ametropia (refractive errors). The most common type of refractive error was astigmatism, followed by myopia; no subjects had hyperopia. In conclusion, the majority of tenth-grade adolescents have normal vision (emmetropia). Among all subjects, astigmatism is the most prevalent refractive error, followed by myopia. Keywords: refractive errors; myopia; astigmatism; adolescents Abstrak: Kelainan refraksi yang tidak terkoreksi menjadi penyebab utama gangguan penglihatan pada semua kelompok usia. Di Indonesia, remaja usia 15-18 tahun menghadapi risiko kesehatan mata akibat penggunaan perangkat elektronik berlebihan, terutama selama masa pandemi COVID-19. Penelitian ini bertujuan untuk untuk mengetahui prevalensi kelainan refraksi pada anak remaja. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan desain potong lintang. Subjek penelitian ini diambil dengan total sampling yaitu siswa kelas X di SMA Rex Mundi Manado yang mengikuti skrining kelainan refraksi dan memenuhi kriteria inklusi, yaitu sebesar 225 responden. Hasil penelitian mendapatkan sebanyak 176 siswa dengan emetropia dan 49 siswa ametropia. Jenis kelainan refraksi terbanyak ialah astigmatisme, diikuti dengan miopia ringan; tidak didapatkan siswa yang mengalami hipermetropia. Simpulan penelitian ini ialah mayoritas remaja kelas X memiliki status refraksi emetropia. Di antara seluruh subjek penelitian, prevalensi kelainan refraksi terbanyak ialah astigmatisme, diikuti dengan miopia ringan Kata kunci: kelainan refraksi; miopia; astigmatisme; remaja